Examining and Expanding the Expectancy Disconfirmation Model: Evidence from Rural China. (12th May 2022) - Wang, Peng; Fan, Fengchun
Abstract : In public management research, the Expectancy Disconfirmation Model (EDM) is increasingly used to measure citizen satisfaction. However, current EDM research in the public sector has been applied primarily in the United States and sets of the city, state, federal, or local government services. It leaves the validity of EDM for other levels and countries of government services to be verified. This study tests and extends the EDM by comparing it with previous studies and adding additional expectation priors to the model. Analysis of survey data from 313 citizens in 6 rural communities in China indicates that the basic model functions well in rural public services. In addition, the study of the extended EDM shows significant relationships between trust, service awareness, bureaucratic responsiveness, and expectations, which suggests new directions for future research using the model.